SCARCITY OF PUBLIC RESOURCES: A READING FROM SOLIDARITY BETWEEN THE FEDERATED ENTITIES AND THE PEOPLE: uma leitura a partir da solidariedade entre os entes federados e as pessoas - Rodrigues, Hugo Thamir (2023)
The objective is to analyze the financial consequences of the Coronavirus’s pandemic (COVID-19), the limits and possibilities of public policies refraining the virus’ dissemination. In such context, the problematic of the research is inserted in the necessity of associating the principle of solidarity betweenMthe State and the people in order to reach effective answers regarding coping with the sanitary crisis. Starting from the data obtained from the Epidemiological Newsletter of week 34 of 2020 from the Ministry of Health and, from the principle of solidarity, the goal was to demonstrate the necessity of conjugating positive behavioral stimuli in defense of the life of each and for everyone. It was shown, from the deductive method and bibliographical and documental research that without the inclusion of the principle of solidarity it is impossible for the State to comply with social protective measures in face of the scarcity of resources. It became evident that, the inclusion of the principle of solidarity as a daily practice is of the most importance for coping with the pandemic and, the joint of forces is crucial for the social balance. At the end, it was detected that, even thoug there are not many fiscal options to reorganize public safes, the State has at its disposal fiscal tools, to perfect the revenue collection and distribution model, in order to materialize rights and, enforce social justice.